Challenges of molecular barcode-based identification of earthworm specimens for biodiversity assessment - Barraux, Andréa; Noël, Shanèze; Roy, Virginie; Dupont, Lise (Frontiers in Ecology and Evolution, 2024)
Specimen identification at the species level is a critical challenge for understanding community structure and conserving biodiversity. The use of mitochondrial DNA barcodes, in addition to morphology, has proven to be a useful tool for earthworm identification, but it has also raised difficulties. Thus, approaches to delineating molecular operational taxonomic units (MOTUs) from cytochrome c oxidase subunit 1 (COI) or 16S rDNA sequence data often reveal more mitochondrial lineages than morphospecies, raising the question of whether these MOTUs should be used as taxonomic entities in community structure studies. Here, we used a newly acquired dataset of 576 COI barcodes of earthworms from Metropolitan France that were clustered in 36 MOTUS, corresponding to 21 morphospecies. We also incorporated data gathered from the literature to investigate this question. In order to match our MOTUs with already-described mitochondrial lineages, we downloaded reference sequences from the GenBank and BOLD platforms. In light of the difficulties encountered in recovering these sequences, we recommend that any new mitochondrial lineage described in a study be named consistently with previous works. Next, we analyzed the biological, ecological, and molecular data available in the literature on the different mitochondrial lineages that matched our MOTUs in order to determine if there was a consensus for species delimitation. Although the study specimens mainly belong to the Lumbricidae, which is one of the most studied families of earthworms, the data are often missing to determine if the MOTUs correspond to different species. Pending revision of the taxonomy, MOTUs for which mitochondrial divergence has been confirmed by morphological differences should be considered distinct taxonomic entities in community structure studies. In the absence of morphological differences and pending more data, we propose to distinguish for these analyses, within sexually reproducing morphospecies, the MOTUs for which mitochondrial divergence has been confirmed by multilocus nuclear data, while in the case of reproduction by parthenogenesis, ecological differences between MOTUs are necessary to consider them as different taxonomic entities.